Amyloid Proteins and Their Role in Multiple Sclerosis. Considerations in the Use of Amyloid-PET Imaging - Matías-Guiu, Jordi A.; Oreja-Guevara, Celia; Cabrera-Martín, María Nieves; Moreno-Ramos, Teresa; Carreras, José Luis; Matías-Guiu, Jorge (Frontiers in Neurology, 2016)
Thioflavin T derivatives are used in positron-emission tomography (PET) studies to detect amyloid protein deposits in patients with Alzheimer disease. These tracers bind extensively to white matter, which suggests that they may be useful in studies of multiple sclerosis (MS), and that proteins resulting from proteolytic processing of the amyloid precursor protein (APP) may contribute to MS. This article reviews data from both clinical and preclinical studies addressing the role of these proteins, whether they are detected in CSF studies or using PET imaging. APP is widely expressed in demyelinated axons and may have a protective effect in MS and in experimental allergic encephalomyelitis in animals. Several mechanisms associated with this increased expression may affect the degree of remyelination in MS. Amyloid-PET imaging may help determine the degree of demyelination and provide information on the molecular changes linked to APP proteolytic processing experienced by patients with MS.